Structural properties of Ti/Al clads manufactured by explosive welding and annealing. (5th February 2016) - Fronczek, D.M.; Wojewoda-Budka, J.; Chulist, R.; Sypien, A.; Korneva, A.; Szulc, Z.; Schell, N.; Zieba, P.
Abstract: The paper presents a comprehensive study on the titanium and aluminum clads manufactured by explosive welding. Particularly, the microstructure evolution of the Al/Ti interface at 825 K and various annealing time was examined. In the state directly after explosive welding, the wavy morphology of the connection was locally composed of four intermetallic phases: TiAl3, TiAl2, TiAl and Ti3 Al, forming small and peninsula-like morphology (vortex). The annealing process mainly caused growth of the TiAl3 phase as a continuous layer. The studies of the growth kinetics showed four stages: incubation period (up to 1.5 h), the growth govern by the chemical reaction (1.5–5 h), mixed mechanism of chemical reaction and volume diffusion and finally the volume diffusion growth (36–100 h). The orientation maps revealed significant differences concerning the microstructure and texture of welded metals. Directly after explosive welding process, aluminum possessed a typical rolled texture, while in titanium intensive twinning was observed. After annealing, due to the secondary recrystallization, abnormal grain growth was observed in aluminum, while in titanium annihilation of deformation twins took place. The hardness profile made across the welded area after annealing showed the highest values between 365–750 HV in vortex regions at the Al/Ti interface. Graphical abstract: The influence of annealing time at 825 K on the explosively welded Ti/Al interface-SEM/EBSD images of sample in the state directly after explosive welding (left) and after 100 h of annealing at 825 K. Standard triangle colors correspond to crystallographic plane parallel to rolling plane (RD, TD). Highlights: Al and Ti clads were joined using explosive welding followed by annealing at 825 K. As a result the Al grain growth and annihilation of deformation twins in Ti took place. Two mechanisms of TiAl3 growth were observed: chemical reaction and volume diffusion. Hardness possessed the highest values for the intermetallic phase of 365 up to 750 HV.